Antecedents of knowledge-sharing behavior in higher education - Husain Nurisman (Inovasi : Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
Knowledge sharing (KS) has been consistently recognized as essential in organizational development and employee improvement. This paper aims to expand on previous empirical research on KS by examining the effect of personality traits (PT) and perceived organizational support (POS) on one's knowledge-sharing behavior in higher education. The authors also examined perceived organizational support's moderating and mediating roles in these relationships. Using a questionnaire and data from 205 lecturers from 3 universities in Jakarta were used for research hypotheses. The results of this study reveal that personality traits (PT) and perceived organizational support (POS) have a significant influence on knowledge-sharing behavior (KS). The results also show that a higher level of perceived organizational support (POS) cannot strengthen the relationship between personality traits (PT) and knowledge-sharing behavior (KS). The teacher's desire to share knowledge can be influenced by the teacher's personality traits and the organization's role in creating supportive conditions. Organizations can provide good welfare and opportunities for their members to develop. This study shows that personality traits (PT) and perceived organizational support (POS) are essential factors influencing a person's desire to share knowledge, especially in higher education.